The jurisdiction structure of the future: a systemic and holistic approach - Jiménez Vivas, Javier Eduardo (2021)
The present and future challenges of the jurisdictional function are also those of the organizations that integrate the justice system and of society as a whole. A jurisdictional response or the response of these organizations alone will be insufficient. A systemic and holistic vision is needed for any policy or management. The education system, the economy and new technologies are three segments clearly committed, but in a transformative way: their communion allows outlining a jurisdictional structure with a different systemic insertion.